Cutaneous silent period recordings in demyelinating and axonal polyneuropathies - İŞAK, BARIŞ (ELSEVIER IRELAND LTD, 2015)
Objective: To investigate the cutaneous silent period (CSP), a spinal inhibitory reflex mainly mediated by A-delta fibres, in demyelinating and axonal polyneuropathy (PNP) and evaluate whether CSP parameters differ between patients with and without neuropathic pain. Methods: Eighty-four patients with demyelinating PNP, 178 patients with axonal PNP and 265 controls underwent clinical examination, DN4 questionnaire, standard nerve conduction study, motor-root stimulation and CSP recordings from abductor digiti minimi. We calculated the afferent conduction time of CSP (a-CSP time) with the formula: CSP latency - root motor evoked potential latency. Results: In the demyelinating PNP group the a-CSP time was significantly longer; in the axonal PNP group, CSP duration was shorter than the demyelinating group (p = 0.010) and controls (p = 0.001). CSP parameters were not different between patients with and without neuropathic pain. Conclusions: The abnormality of a-CSP time in the demyelinating PNP group suggests the crucial role of A-delta fibres in the mechanism of CSP; the shorter CSP duration in the axonal PNP group supports the strong influence of the number of axons on this parameter. Conclusions: Our study suggests that neuropathic pain could be related to pathophysiological mechanisms differing from mere A-delta fibre loss. Significance: CSP evaluation is effective in detecting A-delta fibre dysfunction in axonal as well as demyelinating PNP. (C) 2014 International Federation of Clinical Neurophysiology. Published by Elsevier Ireland Ltd. All rights reserved.
Keywords: Cutaneous silent period; A-delta fibres; Axonal polyneuropathy; Demyelinating polyneuropathy; Neuropathic pain; ROCHESTER DIABETIC-NEUROPATHY; F-WAVE; EFNS GUIDELINES; MIXED NERVE; HAND MUSCLE; PAIN; STIMULATION; MOTOR; SENSITIVITY; DIAGNOSIS